2004
DOI: 10.1017/s1352465804001018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Treatments for Children With Severely Disruptive Behaviours: A Four-Year Follow-Up

Abstract: A 4-year follow-up compared the long-term effects of two treatments for severely conduct disorder children referred to a Child and Adolescent Mental Health Service (CAMHS). Forty-two families received either the standard CAMHS treatment or a more intensive intervention. The intensive treatment involved a unit-based component for parents to practise new child management strategies. At the 6-month follow-up the intensive treatment group showed significant improvements on all measures of child behaviour and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
1
40
1
2
Order By: Relevance
“…While we know of no long-run randomised evaluation of the IY programme, the evidence available does suggest that the initial gains reported for the IY programme may have a significant longer-run component. Hutchings et al [48] report on a 4-year follow-up evaluation of a structured parenting programme, which is similar in many ways to the IY programme. They found that the substantial improvements in child behaviour observed after the 6-month follow-up were still evident four years after the intervention had stopped.…”
Section: Discussionmentioning
confidence: 99%
“…While we know of no long-run randomised evaluation of the IY programme, the evidence available does suggest that the initial gains reported for the IY programme may have a significant longer-run component. Hutchings et al [48] report on a 4-year follow-up evaluation of a structured parenting programme, which is similar in many ways to the IY programme. They found that the substantial improvements in child behaviour observed after the 6-month follow-up were still evident four years after the intervention had stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Patterson et al, 2005), parents also emphasized increased personal confidence as being important in removing guilt and isolation and instilling selfefficacy beliefs-factors that are likely to be important in maintaining positive outcomes over time (Hutchings, Lane & Kelly, 2004;Hutchings, Bywater, Williams & Whitaker, in submission). Although RCTs typically demonstrate that the IYP improves parental mental health, only one study (Gardner et al, 2006) has investigated the mediating impact of parental mood.…”
Section: Discussionmentioning
confidence: 99%
“…Group-based parenting programs are typically manualized and structured interventions, underpinned by a range of theoretical approaches (including behaviorism and cognitive behavioral therapy). Although the content and delivery of such programs can and do vary (Hutchings, Lane, & Kelly, 2004;Sanders & McFarland, 2000), the programs typically use a range of strategies-including discussions, activities, videotaped demonstrations, and modeling of parenting behaviors-which are delivered in 2-hour sessions over a programs that range from 4 to 12 weeks. Reviews of qualitative evidence point to a range of benefits of participating in a group with other parents (Kane, Wood, & Barlow, 2007).…”
mentioning
confidence: 99%